PENGARUH UKURAN UTAMA KAPAL TERHADAP DISPLACEMENT KAPAL - Budi Utomo (TEKNIK, 2010)
Displacement is weight water which is replaced ship hull. The displacement influenced by dimension of inmerchant ship. The displacement musat be small as posible, but the capacity and the speed must be pullfill.Dsplacement can be obtained by formulation or by experiment in hydrodinamika laobatory, the modelingcharacteristic us descube the real Calculation of the ship.The form of the ship must give the resistaise as small as posible. In athe hard the capacity must be full fill ofload